SALARY PREDICTION OF IT EMPLOYEES IN JAVA USING LINEAR REGRESSION ALGORITHM - Rudy Chandra; Tegar Arifin Prasetyo; Sarbaini Sarbaini (Lambung Mangkurat University, 2023)
The payroll system is very influential on a company's workers' welfare in achieving company goals. Appropriate payroll will build morale for the workforce so that they can advance the company through the work ethic and professionalism of the crew. The salary calculation system for employees must be adjusted to several criteria, such as their city and job role. Long experience can also be used as a calculation criterion in providing salary. For this reason, an approach is needed to provide a decent and good salary prediction for the company's consideration. One of the models commonly used in making predictions is linear regression. Linear regression is a model that calculates the relationship between two variables with independent values and bound data. This research develops a system by implementing a Linear Regression algorithm to predict the salaries of IT employees in Java. The model that has been created is then built using the Python language and implemented into a website-based visualization form that is easy to understand with Streamlit. The modeling results were tested and gave an MSE value of 8240258.48. This research is expected to be a reference in research related to this topic in the future and can be used by companies that have difficulties in determining employee salaries